Pengembangan Modul Larutan Elektrolit dan Non Elektrolit Berbasis Pendekatan Saintifik dengan Pertanyaan Probing Prompting untuk Kelas X SMA atau MA - Dini Yuliantika; Ellizar Ellizar (Edukimia, 2019)
Curriculum 2013 equires learning to be able to improve students activeness and thinking skills. One effort that can be done is by giving probing prompting questions. This study aims to develop module of electrolyte and non-electrolyte solutions based on a scientific approach with each step containing probing prompting questions. The type of research used is R and D (Research and Development) through the stages of 4-D development model. The research phase carried out include 1) define phase, 2) design stage, 3) develop stage and disseminate stage. However, the research is limited to develop stage. The module developed was tested for validity and practicality through the provision of questionnaires and processed using Cohen kappa formula. Based on the results of the study of validity tests on 5 validators (2 lecturers and 3 teachers), the kappa moment was 0.86 with very high validity. Meanwhile, based on the practicality test conducted at SMAN 1 2x11 Enam Lingkung by 3 teachers and 29 students, each kappa moment was 0.89 and 0.86. This shows that the module of electrolyte and non-electrolyte solutions based on the scientific approach using probing prompting for grade X SMA or MA has been valid and practical to be used in the learning process.